Peran Ganda Istri dalam Budaya Patriarki: Analasis Kesetaraan Gender dan Perspektif Maqasid Syariah - Nurhaidah Siregar; Uswatun Hasanah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The phenomenon of the dual role of wives is a complex social reality amidst the patriarchal culture that is still deeply rooted in Indonesian society. In this social system, women often bear the double burden of domestic responsibilities as well as public roles, which often gives rise to gender inequality, role conflict, and psychological stress. This article aims to analyze the dual role of wives in a patriarchal culture using a gender perspective and maqasid sharia as an analytical framework. The research method used is a literature study with a qualitative-descriptive approach to various relevant literature. The results of the study indicate that patriarchal culture tends to limit access and recognition of women's roles, thus contradicting the principle of gender justice. Meanwhile, maqasid sharia emphasizes the values ​​of balance, justice, and benefit in husband-wife relations. The principles of hifz ad-din, hifz an-nafs, hifz al-aql, hifz an-nasl, and hifz al-mal provide theological legitimacy for women's social and economic roles as long as they are carried out within the framework of justice, shared responsibility, and family harmony.